Mapeamento proteico da matriz do esmalte de incisivos de camundongos susceptíveis e resistentes à fluorose dentária - Leite, Aline de Lima (Universidade Federal de São Carlos, 2015)
Enamel formation is a two-step complex process by which proteins are first secreted to forming an extracellular matrix, followed by massive protein degradation simultaneously with the completion of mineralization. Excessive exposure to fluoride can disrupt this process and drive to a condition known as dental fluorosis. Recently it has been reported that genetic factors may influence the responses of mineralized tissues to fluoride, a phenomenon observed in A/J and 129P3/J mice strain. The present study aimed to map the protein profile of mouse enamel. Enamel matrix samples were obtained from A/J and 129P3/J mice and analyzed by two-dimensional electrophoresis and liquid chromatography, coupled to mass spectrometry. A total of 120 proteins were identified, from which 113 are well characterized, both experimentally and functionally. Seven proteins were classified as uncharacterized proteins. After functional enrichment, 9 proteins were significantly related to the terms "odontogenesis and tissue biomineralization”. Surprisingly, the COL1A1 and COL1A2 protein were found on secretory stage enamel of both strains. Protein interaction analysis showed interaction between the ENAM and other types of collagen. Another interesting finding was the possibility of uncharacterized sequence Q8BIS2 be an extracellular matrix protein involved on degradation of matrix proteins. These findings suggest that collagen is present on dental enamel and it seems to have a role in amelogensis. Furthermore, the existence of an new enzyme could be the key to elucidation of the mechanisms involved in the enamel biomineralization and the genetic susceptibility to dental fluorosis.
Keywords: Genética; Amelogênse; Proteômica; Esmalte dentário; Fluorose dentária; Biomineralização; Fluoride; Proteomic analysis; Amelogenesis; Fluorosis; Biomineralization; CIENCIAS BIOLOGICAS::BIOQUIMICA::BIOLOGIA MOLECULAR; CIENCIAS BIOLOGICAS::GENETICA